2020
DOI: 10.1107/s2053230x1901642x
|View full text |Cite
|
Sign up to set email alerts
|

The adhesive PitA pilus protein from the early dental plaque colonizerStreptococcus oralis: expression, purification, crystallization and X-ray diffraction analysis

Abstract: PitA is the putative tip adhesin of the pilus islet 2 (PI-2)-encoded sortase-dependent pilus in the Gram-positive Streptococcus oralis, an opportunistic pathogen that often flourishes within the diseased human oral cavity. Early colonization by S. oralis and its interaction with Actinomyces oris seeds the development of oral biofilm or dental plaque. Here, the PI-2 pilus plays a vital role in mediating adherence to host surfaces and other bacteria. A recombinant form of the PitA adhesin has now been produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As one of the earliest colonized bacteria, oral Streptococcus has stronger adhesion than the later colonized bacteria, so it may be more difficult to remove during oral cleaning. The proportion of Lactobacillus in the whole oral flora is very small, usually about 0.01%-1% (13). Yang Ran et al found that the detection rates of Actinomyces odontolyticus and Actinomyces naeslundii in a caries-free group were significantly higher than those in a caries-sensitive group, and speculated that Actinomyces odontolyticus and Actinomyces naeslundii may be cariesbeneficial bacteria (14).…”
Section: Luo Et Almentioning
confidence: 99%
“…As one of the earliest colonized bacteria, oral Streptococcus has stronger adhesion than the later colonized bacteria, so it may be more difficult to remove during oral cleaning. The proportion of Lactobacillus in the whole oral flora is very small, usually about 0.01%-1% (13). Yang Ran et al found that the detection rates of Actinomyces odontolyticus and Actinomyces naeslundii in a caries-free group were significantly higher than those in a caries-sensitive group, and speculated that Actinomyces odontolyticus and Actinomyces naeslundii may be cariesbeneficial bacteria (14).…”
Section: Luo Et Almentioning
confidence: 99%
“…Characteristically, the formation of these covalent bonds requires triad-sequestered Lys and Asn/Asp residues and an autocatalytic glutamate (or aspartate) in a hydrophobic environment. Among the three pilin types, the adhesive tip subunits are the largest, consisting of an N-terminal receptor-binding region that is often a globular domain and a C-terminal stalk-like region of CnaA/ CnaB domains (Izoré et al, 2010;Kant et al, 2020;Linke-Winnebeck et al, 2014;Pointon et al, 2010;Kumari Yadav & Krishnan, 2020). Backbone subunits typically consist of two to four CnaA/CnaB domains (Krishnan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Finally, Tb-Xo4 was exploited to determine new protein structures including multi-protein complexes [20][21][22] and can be used as a routine nucleating and phasing tool by the community. [23][24][25][26][27] To understand the origins of the crystallophore nucleating and phasing properties with the aim to further improve them, we analyzed the binding of Tb-Xo4 at the surface of proteins by coupling crystal structure analysis, obtained on 4 different proteins, with evaluation of the interaction energies determined by density functional theory calculations. 28 This detailed analysis of the interaction sites on the proteins surfaces clearly demonstrated the great versatility of Tb-Xo4 binding through various supramolecular interactions via anionic, cationic or hydrophobic amino-acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…The story so far of the Xo4 system started with its terbium variant Tb-Xo4. Its unique properties were first highlighted with a set of eight proteins, and its efficiency was confirmed in solving issues often dealt by crystallographers in their quest to assess the protein structure. , Finally, Tb-Xo4 was exploited to determine new protein structures including multiprotein complexes and can be used as a routine nucleating and phasing tool by the community. …”
Section: Introductionmentioning
confidence: 99%